The effects of creatine loading and gender on anaerobic running capacity - Fukuda, D. H.; Smith, A. E.; Kendall, K. L.; Dwyer, T. R.; Kerksick, C. M.; Beck, T. W.; Cramer, J. T.; Stout, J. R. (The Journal of Strength and Conditioning Research, 2010)
Creatine (Cr) loading consists of short-term, high-dosage Cr supplementation and has been shown to increase intramuscular total Cr content. Increases in body weight (BW) have been shown to result from Cr loading, with differences by gender, and increased BW may impact weight-bearing exercise. The critical velocity (CV) test is used to quantify the relationship between total running distance and time to exhaustion. The CV test provides the variable, anaerobic running capacity (ARC), which is an estimate of the anaerobic energy reserves in muscle. The purpose of this study was to examine the effects of gender and Cr loading on ARC. Fifty moderately trained men and women volunteered to participate in this randomized, double-blinded, placebo (PL)-controlled, repeated-measures study. After a familiarization session, a 3-day testing procedure was conducted. A maximal oxygen consumption test (V.O2max) on a treadmill was performed on day 1 to establish the maximum velocity (Vmax) at V.O2max and to record BW. Days 2 and 3 involved treadmill running at varying percentages of Vmax. Participants were randomly assigned to either the Cr or PL group and received 20 packets of the Cr supplement (1 packet = 5 g Cr citrate, 18 g dextrose) or 20 packets of the PL (1 packet = 18 g dextrose). After consuming 4 packets daily for 5 consecutive days, the 3-day testing procedure was repeated. The male Cr loading group exhibited a 23% higher (p = 0.003) ARC compared to the PL group. Nonsignificant BW increases were found for the Cr groups. These findings suggest that Cr loading may be an effective strategy for improving ARC in men, but not in women, and revealed only nonsignificant increases in BW. Creatine loading may be used before competition by athletes to provide improvements in high-intensity, short-duration activities.